SISTEM PENUNJANG KEPUTUSAN PEMILIHAN INDUK AYAM KUB TERBAIK DENGAN METODE FUZZY DAN VIKOR - Muhammad Teguh; Sri Setyaningsih; Mulyati . (KOMPUTASI, 2020)
Kampung Unggul Superior Chicken (KUB) is a native native chicken selection from the Animal Research Center (Balitnak). KUB chicken has the advantage of low incubation and high egg production, so it becomes a parent producer of many DOC (female line). Currently consumption of native chicken meat and eggs in the community from year to year has increased while its production has not been able to fully meet the needs of the community. Some of the problems in maintaining KUB hens are not optimal body weight, length of time in laying eggs and even a small amount of egg production quality from selected prospective broodies originating from KUB hens who have high productivity in laying eggs. to overcome these problems, an application system is needed, one of which is a decision support system application. This application can provide recommendations in the selection of the best KUB hens so that the hens can be maintained intensively so that the supply of chicken meat and eggs can meet the needs of the community. There are several methods that can be used to determine the selection of the best KUB Parent, including using the Vikor method. Vikor is used to overcome the problem of complex multi-criteria systems that focus on ranking and selection of an alternative, while to determine the weighting using the Fuzzy Method. The results of this study are in the form of an application system that can help breeders / enclosure technicians in determining the selection of the Best KUB Chicken Parent. The level of system accuracy using the Vikor and Fuzzy methods was obtained at 77.2% of the 9 test data used.